Anti-Foc RT4 Activity of a Newly Isolated Streptomyces sp. 5–10 From a Medicinal Plant (Curculigo capitulata) - Yun, Tianyan; Zhang, Miaoyi; Zhou, Dengbo; Jing, Tao; Zang, Xiaoping; Qi, Dengfeng; Chen, Yufeng; Li, Kai; Zhao, Yankun; Tang, Wen; Huang, Jiaquan; Wang, Wei; et al. (Frontiers in Microbiology, 2021)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense (Foc) is a disastrous soil-borne fungal disease. Foc tropical race 4 (Foc TR4) can infect almost all banana cultivars. Until now, there are short of safety and effective control methods and commercial banana cultivars with a resistance against Foc TR4. Biocontrol using environmentally friendly microbes is a promising strategy for the management of Foc TR4. Here, a strain 5-10 newly isolated from a medicinal plant (Curculigo capitulata) exhibited a high antifungal activity against Foc TR4. Combing the morphological characteristics and molecular identification, strain 5-10 was classified as Streptomyces genus. The sequenced genome revealed that more than thirty-nine gene clusters were involved in biosynthesis of secondary metabolites. Some multidrug resistance gene clusters were also identified such as mdtD, vatB and vgaE. To improve anti-Foc TR4 activity of strain 5-10 extracts, an optimization method of fermentation broth was established. Antifungal activity increased by 72.13% under the fermentation system containing 2.86 g/L of NaCl and 11.57% of inoculation amount. After treated with strain 5-10 extracts, the Foc TR4 hyphae became shrink, deform and rupture. The membrane integrity and cell ultrastructure incurred irreversible damage. Streptomyces sp. 5-10 extracts play a fungicidal role in Foc TR4. Hence, Streptomyces sp. 5-10 will be a potential biocontrol agent to manage fungal diseases by exploring the microbial fertilizer.